(untitled) (Journal of Economic Research & Business Administration, 2016)
The relevance of accounting issues to be addressed in any society. At this time, all States and continents came to the conclusion that it is necessary to compare and make related national accounting system, and to resume all his strength. Therefore, the article considers the relationship between theory and practice of accounting by studying the works of a number of domestic and authors on this issue, the author defends their viewpoint and justify their meaning and difference. The originality of this research lies in the scientific results, which justifies the link between ac-counting theory and practice, and specific suggestions and vision of the author.